Profile and Perception of Retail Consumers - An Empirical Study in Palakkad District - Ashokan, C.; Hariharan, G. (Indian Journal of Marketing, 2008)
Retailing is considered the world’s largest industry with US 6.6 trillion sales annually. The retailing industry in India is worth around 300b. There are around 5 million retail outlets of all sizes and styles. The retail market is likely to increase by 20% annually. As much as 96 % of the 5 million-plus outlets are smaller than 500 square feet area. This means that India per capita retailing space is about 2 square feet compared to 16 square feet in the United States. Just over 8 % of India’s population is engaged in retailing. (20% in USA). People flock to the outlets for convenience, merchandise, and for enjoying the shopping and entertainment experience. This article attempts to bring out the profile and perception of consumers’ shopping at two leading retail outlets of Palakkad District; Spencer’s’ Daily and Big Bazaar. Kerala’s retail market is dominated by Margin Free Markets, Supplyco and local Kirana Stores. With the arrival of new-generation stores like Spencer’s Big Bazaar, etc, the shopping habits of Keralites is changing. The present study throws light on that vital aspect. The study focuses on three parts, the profile of the consumers, their preferences and the satisfaction level of the shoppers.